Investigating the mechanisms of glyphosate resistance in goosegrass (Eleusine indica) population from South China - Chun ZHANG; Li FENG; Ting-ting HE; Cai-hong YANG; Guo-qi CHEN; Xing-shan TIAN (Journal of Integrative Agriculture, 2015)
Glyphosate has been used worldwide for nearly 40 years, and 30 types of resistant weeds have been reported. Glyphosate is mass-produced and widely used in China, but few studies and reports on glyphosate-resistant weeds and resistance mechanisms exist. Previous studies found a goosegrass species with high glyphosate resistance from orchards in South China and its glyphosate resistant mechanism was described in this study. The cDNA of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS, EC 2.5.1.19), the target enzyme of glyphosate, was cloned from the glyphosate-resistant and -susceptible goosegrass, respectively, and referred as EPSPS-R and EPSPS-S. The Pro106 residue was known to be involved in the glyphosate resistance in most goosegrass populations. However, sequence analysis did not find the mutation at the Pro106 residue in the R biotype EPSPS amino acid sequence. The residue 133 and 382 was mutated in the R biotype EPSPS amino acid sequence instead, but it did not affect the EPSPS-S and EPSPS-R genes sensitivities to glyphosate. RT-PCR and Western blot analyses suggested that EPSPS mRNA and protein are mainly present in the shoot tissues both in the R and S goosegrass biotypes. The EPSPS-R rapidly responds to the glyphosate in R-biotype goosegrass and the induced expression was detected at 12 h post glyphosate treatment. The mRNA and protein expression of EPSPS-R increased constantly as the increasing concentration of glyphosate. However, the expression of the EPSPS-S was not induced significantly by glyphosate in the S goosegrass biotype. Quantification of real-time PCR results showed that the copy number of the EPSPS in R-biotype goosegrass was 4.7 times higher than that in the S goosegrass biotype. All the results implied that EPSPS gene amplification might mainly caused the glyphosate resistance of a goosegrass population collected from orchards in South China.